IMPLEMENTASI KAMPANYE HEALTHY LIFESTYLE GREAT GIANT FOODS SELAMA PANDEMI COVID-19 MELALUI INSTAGRAM @GREATGIANTFOODS - Dilla Savira (2022)
This study aims to discuss the implementation of the Healthy Lifestyle campaign activities which were carried out online through the social media Instagram @greatgiantfoods by Great Giant Foods (GGF) during the Covid-19 pandemic using a supporting model, namely the Nowak Warneryd Campaign Model and the Campaign Management Model. The method used in this research is descriptive qualitative method using primary data and secondary data sources. Researchers collected data independently through behavioral observations, interviews with relevant sources, and documentation. The researcher uses four stages of data analysis according to Miles & Huberman, namely data collection, data reduction, data presentation, and drawing conclusions using the data validity technique of triangulation. After going through the process of research and interpretation, the results of this study indicate that the Healthy Lifestyle campaign carried out by GGF has gone through the stages in accordance with the campaign management model popularized by Antar Venus, namely, the stages of planning, development, implementation, monitoring, and evaluation. The implementation of the Healthy Lifestyle campaign was carried out to have an impact on the target audience in the form of knowledge and provide awareness that the application of a healthy lifestyle is very important, especially when Covid-19 pandemic. The researcher also found that GGF carried out trial and error in the publication of its campaign messages and carried out regular monitoring and evaluation to see the possibility of campaign success. Keywords: Covid-19, Healthy Lifestyle, Instagram, Campaign, social media